Digital Literacy-Based Learning Video on the Topic of Natural Resources and Technology for Grade IV Elementary School - Ni Luh Paramita Cahyani; I Nyoman Laba Jayanta (Universitas Pendidikan Ganesha, 2021)
The lack of availability of innovative learning media that is able to load material effectively has an impact on the low motivation to learn and students' understanding of the material. This study aims to design a digital literacy-based learning video media on the topic of natural resources and technology for grade IV SD which has been tested for validity. This research is development research or RnD (research and development). This development research uses the ADDIE model. The subjects in this study consisted of 2 material experts, 2 media experts, 2 practitioners, 6 students in two elementary schools for individual trials, and 12 students in two elementary schools for small group trials. The data collection method used is the questionnaire method with the distribution of rating scale instruments on a scale of 5. The data from the assessment results that have been obtained are then analyzed by the Mean formula to obtain the average score. The average score of material experts is 4.73, media experts are 4.50, practitioners are 4.78, individual trials are 4.53 and small group trials are 4.61. So, overall the results of the validity of the digital literacy-based learning video media are in the range of 4.01 < x < 5.01 with very good qualifications. Based on this analysis, digital literacy-based learning video media on the topic of natural resources and technology for fourth-grade elementary school are feasible to be used in the learning process.